2007
DOI: 10.1111/j.1553-2712.2007.tb01757.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison Trial of Case-based Learning versus Human Patient Simulation in Medical Student Education

Abstract: Objectives: Human patient simulation (HPS), utilizing computerized, physiologically responding mannequins, has become the latest innovation in medical education. However, no substantive outcome data exist validating the advantage of HPS. The objective of this study was to evaluate the efficacy of simulation training as compared with case-based learning (CBL) among fourth-year medical students as measured by observable behavioral actions.Methods: A chest pain curriculum was presented during a one-month mandator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 25 publications
1
21
0
3
Order By: Relevance
“…For example, one study found a positive impact of simulation on specific cardiac and pulmonary diagnostic skills for first year medical students (11) and another on the physiological effects of anesthetic agents on hemodynamic parameters (12). As described earlier, most simulation medical school interventions like ours have focused on third- and fourth-year students in clerkships like emergency medicine (1315, 18, 19), surgery (16), and anesthesia (17). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study found a positive impact of simulation on specific cardiac and pulmonary diagnostic skills for first year medical students (11) and another on the physiological effects of anesthetic agents on hemodynamic parameters (12). As described earlier, most simulation medical school interventions like ours have focused on third- and fourth-year students in clerkships like emergency medicine (1315, 18, 19), surgery (16), and anesthesia (17). …”
Section: Discussionmentioning
confidence: 99%
“…Unlike many previous studies (1315), the primary intent of this study was to assess whether simulation had an additive benefit to a traditional curriculum rather than as a replacement to existing formats such as lectures or problem-based learning (PBL) sessions. Our intention was to use the simulation experience for experiential learning (6) and deliberate practice (7, 8) as a method for reinforcing key teaching points that were emphasized in the lectures and PBL cases.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed by Schwartz et al 34 in 2005 assessed the performance of fourth-year medical students after a month of instruction during their required EM clerkship by using either a Human Patient Simulator (HPS) or Case-based Learning (CBL) modules. The students were randomly assigned to either the CBL (n = 52) or HPS (n = 50) groups, and each group was taught a chest-pain curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature addressing improved student performance may be inconclusive, 1620 simulation has been shown to have a positive impact in a number of other trainee groups. 2124 Incorporating high-fidelity simulation into emergency medicine clerkships allows reproduction of physiologic extremes, and students can practice critical care scenarios for critically ill patients without interruption from faculty.…”
Section: Discussionmentioning
confidence: 99%